Characterization of the intestinal microbiota of natural populations of Lutzomyia evansi: vector of visceral Leishmaniasis (2016)
Lutzomyia evansi (Diptera: Psychodidae) is a phlebotomine “sandfly” insect endemic to the Caribbean coast of Colombia with epidemiological significance for being the main vector of leishmaniasis disease, which is caused by Leishmania spp parasites. Sand flies (164 species in Colombia) in general are able to transmit other parasites as Bartonella spp, and virus mostly from vesiculovirus group, affecting human and animal health. This group of insects has been studied in Colombia in relation to vectorial role, geographical distribution and epidemiological importance, but vaccine absence for the most important disease they transmit (leishmaniasis) encourage the implementation of vector control measures as key factor for the disease control. In this sense entomological surveillance and prevention measures have been implemented but most of the time in transmission episodes is frequently invested in taxonomical work. In spite of the importance of phlebotomine sand flies and the necessity of their control, very few studies exist in Colombia and in general in America, related to their biology, ecology or many other basic aspects, which are relevant for their diminishing or control. Biological control of insect vectors or the parasites or pathogens they transmit is a topic of research actually addressed by academic and scientific points of view and encouraged by health authorities given difficulties as insecticide resistance and costs for traditional methods. For Lutzomyia spp., sand flies, this is one basic study providing, basic information about microbial communities (bacteria) associated to their biological stages (larvae, pupa and adult) and evaluating as basic line of evidence, potential effects of some of them on Lesihmania. Although Lu evansi and in general sandflies can harbor pathogenic and non-pathogenic microorganisms in their guts, there is little knowledge related to the intestine ecology and to the bacterial diversity present in the gut of wild populations. Presence of some bacteria including Wolbachia spp is of significance and may encourage further investigation on the possible effects of those bacteria in Leishmania transmission given the proven effect on some viruses and other parasites in their vectors. In this study, conventional microbiological methods and molecular ones, were used to explore the composition of bacterial communities associated with the gut of immature and adult stages of wild populations of Lu. evansi from the department of Sucre (Caribbean coast of Colombia). Different lines of evidence were addressed for identification of the bacteria including ribosomal intergenic spacer analysis (RISA) and 16S rRNA and gyrB gene sequences variation. The genetic profile of bacterial populations was generated and compared by temperature gradient gel electrophoresis (TTGE) from total DNA of Lutzomyia gut. Concomitant Wolbachia and Leishmania infection in Lu. evansi and other species was also evaluated by PCR. Leishmanicidal and antimicrobial activity of Pantoea ananatis, Ochrobactrum anthropi and Enterobacter cloacae, isolated from the gut of Lu. evansi, were evaluated as well as the sensitivity of these bacteria to commonly used antibiotics. The culture-dependent techniques indicated intestinal bacteria belonging to Acinetobacter, Enterobacter, Pseudomonas, Ochrobactrum, Shinella and Paenibacillus being the dominant bacteria larvae. Lysobacter, Microbacterium, Streptomyces, Bacillus and Rummeliibacillus were found in pupae; Staphylococcus, Streptomyces, Brevibacterium, Acinetobacter, Enterobacter and Pantoea were isolated from adults. Fingerprint pattern of PCR - TTGE had statistical significant variations in bacterial communities in Lu. evansi when immature and adult stages were compared, as also when engorged condition and origin of insects were considered. Results indicated 20% of infection by Wolbachia in all samples of Lutzomyia evaluated. This endosymbiotic bacteria was found in three species: Lutzomyia cayennensis and Lutzomyia dubitans with 3 positive pools= 8.5% for both species, and Lutzomyia evansi, with a positive pool= 2.8%. Two Wolbachia genotypes (strains) were clearly found, wLev in Lu dubitans, Lu cayennensis, and Lu evansi; while wLcay was found only in Lu cayennensis. Evidence of Wolbachia infections in natural Lutzomyia populations encourage further investigation on the possible effects of this bacteria in Leishmania transmission given the proven efficacy in biological control of some parasites transmitted by vectors. The highest percentage of inhibition against Leishmania procyclic promastigotes was observed with bacterial concentrations of 108 CFU/ml of E. cloacae (77.29 ± 0.6%) and P. ananatis (70.17% ± 1.1). The inhibitory growth activity of procyclic L. infantum promastigotes shown by extracts of E. cloacae and P. ananantis suggests that the presence of these bacteria in the vector intestine could be affecting the parasite development to metacyclic stages infective to human hosts, which will be desirable to corroborate. O. anthropi was the isolate with the highest number of antibiotic resistance patterns while P. ananatis and E. cloacae showed greater sensitivity to the antibiotics evaluated.